Post-Stroke Depressive Symptoms: Varying Responses to Escitalopram by Individual Symptoms and Lesion Location. (November 2021) - Lee, Eun-Jae; Kim, Jong S.; Chang, Dae-Il; Park, Jong-Ho; Ahn, Seong Hwan; Cha, Jae-Kwan; Heo, Ji Hoe; Sohn, Sung-Il; Lee, Byung-Chul; Kim, Dong-Eog; Kim, Hahn Young; Kim, Seongheon; et al.
Objective: The efficacy of antidepressants in post-stroke depressive symptoms (PSD) varies. We aimed to examine whether the effect of escitalopram on PSD differs according to individual depressive symptoms and stroke lesion location. Methods: This is a post hoc analysis of EMOTION (ClinicalTrials.gov, NCT01278498), a randomized, placebo-controlled, double-blind trial that examined the efficacy of escitalopram on depression in acute stroke patients (237 with placebo, 241 with escitalopram). Depressive symptoms were evaluated with the 10-item Montgomery-Åsberg Depression Rating Scale (MADRS). Changes in MADRS and individual item scores at 12 weeks were compared between the treatment groups and among the stroke lesion location groups. Stroke lesion locations were grouped according to the anatomical distribution of serotonin fibers that originate from the midbrain/pons and spread to the forebrain via subcortical structures: "Midbrain-Pons, " "Frontal-Subcortical, " and "Others." Least-squares means were calculated to demonstrate the independent effect of lesion location. Results: Total MADRS scores decreased more significantly in the escitalopram than in the placebo group, while a significant effect of escitalopram was observed in only 3 items: apparent sadness, reported sadness, pessimistic thoughts. In the lesion location analyses, escitalopram users in the Frontal-Subcortical group showed significant improvement in total MADRS scores (placebo [n = 130] vs. escitalopram [n = 148], least-square mean [95% CI]: -2.3 [-3.5 to -0.2] vs. -4.5 [-5.5 to -3.4], p = .005), while those in the Midbrain-Pons and Others groups did not. Conclusions: The effect of escitalopram on PSD may be more prominent in patients with particular depressive symptoms and stroke lesion locations, suggesting the need for tailored treatment strategies.